Hydrogen addition can accelerate propionate degradation kinetics during in situ biomethanation - M. Mahieux; L. Braga-Nan; E. Desmond-Le Quéméner; Q. Aemig; C. Richard; J.-P. Delgenès; M. Juge; E. Trably; R. Escudié; G. Capson-Tojo (Chemical Engineering Journal, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Introducing Elinor for monitoring the governance and management of area‐based conservation - Shauna L. Mahajan; Samson Obiene; Lenice Ojwang; Nasser Olwero; Abel Valdivia; Adaoma Wosu; Emily Adrid; Dominic A. Andradi‐Brown; Gildas Andriamalala; Natalie C. Ban; Nathan J. Bennett; Jessica Blythe; et al. (Conservation Biology, 2024)
Monitoring the governance and management effectiveness of area‐based conservation has long been recognized as an important foundation for achieving national and global biodiversity goals and enabling adaptive management. However, there are still many barriers that prevent conservation actors, including those affected by governance and management systems from implementing conservation activities and programs and from gathering and using data on governance and management to inform decision‐making across spatial scales and through time. We explored current and past efforts to assess governance and management effectiveness and barriers actors face in using the resulting data and insights to inform conservation decision‐making. To help overcome these barriers, we developed Elinor, a free and open‐source monitoring tool that builds on the work of Nobel Prize winner Elinor Ostrom to facilitate the gathering, storing, sharing, analyzing, and use of data on environmental governance and management across spatial scales and for areas under different governance and management types. We consider the process of codesigning and piloting Elinor with conservation scientists and practitioners and the main components of the assessment and online data system. We also consider how Elinor complements existing approaches by addressing governance and management in a single assessment at a high level for different types of area‐based conservation, providing flexible options for data collection, and integrating a data system with an assessment that can support data use and sharing across different spatial scales, including global monitoring of the Global Biodiversity Framework. Although challenges will continue, the process of developing Elinor and the tool itself offer tangible solutions to barriers that prevent the systematic collection and use of governance and management data. With broader uptake, Elinor can play a valuable role in enabling more effective, inclusive, and durable area‐based conservation.

Resource recovery using enriched purple phototrophic bacteria in an outdoor flat plate photobioreactor: Suspended vs. attached growth - Gabriel Capson-Tojo; Albie Zuo Meng Gan; Pablo Ledezma; Damien J. Batstone; Tim Hülsen (Bioresource Technology, 2023)

Expanding mechanistic models to represent purple phototrophic bacteria enriched cultures growing outdoors - Gabriel Capson-Tojo; Damien J. Batstone; Tim Hülsen (Water Research, 2023)

Three years in the dark: life history and trophic traits of the hyporheic stonefly, Alloperla ishikariana Kohno, 1953 (Plecoptera, Chloroperlidae) - J. N. Negishi; M. K. Alam; M. A. T. M. T. Rahman; R. Kawanishi; H. Uno; G. Yoshinari; K. Tojo (Hydrobiologia, 2022)

Age‐dependent distribution of juvenile southern bluefin tuna ( Thunnus maccoyii ) on the continental shelf off southwest Australia determined by acoustic monitoring - KENTARO HONDA; ALISTAIR J. HOBDAY; RYO KAWABE; NAOKI TOJO; KO FUJIOKA; YOSHIMI TAKAO; KAZUSHI MIYASHITA (Fisheries Oceanography, 2010)
Juvenile southern bluefin tuna ( Thunnus maccoyii , SBT) were monitored in nearshore waters off southwest Australia using acoustic tagging and monitoring over five austral summers (2002/2003–2006/2007) to determine patterns in age‐based distribution of SBT. A total of 20–70 receivers were deployed in early December along one to three cross‐shelf transects and at three inshore topographic features (lumps) where SBT are known to occur; and a total of 59–84 juvenile SBT (41–90 cm fork length) were tagged and released each year. After several months, receivers were recovered, and data extracted. In 2002/2003 and 2003/2004, 2‐yr‐old SBT were detected more frequently in nearshore areas than did 1‐yr old fish. Similarly in 2004/2005 and 2006/2007, it was the larger 1‐yr‐old SBT that were detected more frequently at inshore lumps (>85% of detections) while small 1‐yr‐old SBT were detected more widely over the study area. In 2005/2006, although large 1‐yr‐old SBT were still detected more frequently at inshore lumps than small 1‐yr old SBT, the percentage of all detections at lumps was lower at 31.5%, indicating wider distribution of both small and large age‐1 fish. The observed age‐dependent distribution pattern may be enhanced by the distribution of prey, which disperse or concentrate depending on the local oceanography.

Attempts at oral pharmacological treatment of Ichthyophthirius multifiliis in rainbow trout, Oncorhynchus mykiss (Walbaum) - J L Tojo Rodriguez; M T Santamarina Fernandez (Journal of Fish Diseases, 2001)